In vivo and in vitro evaluation of an Acetobacter xylinum synthesized microbial cellulose membrane intended for guided tissue repair - Mendes, Pericles Nobrega [UNESP]; Rahal, Sheila Canevese [UNESP]; Marques Pereira-Junior, Oduvaldo Camara [UNESP]; Fabris, Viciany Erique [UNESP]; Rahal Lenharo, Sara Lais; de Lima-Neto, Joao Ferreira [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP] (Biomed Central Ltd., 2009)
Background: Barrier materials as cellulose membranes are used for guided tissue repair. However, it is essential that the surrounding tissues accept the device. The present study histologically evaluated tissue reaction to a microbial cellulose membrane after subcutaneous implantation in mice. Furthermore, the interaction between mesenchymal stem cells and the biomaterial was studied in vitro to evaluate its ability to act as cellular scaffold for tissue engineering.Methods: Twenty-five Swiss Albino mice were used. A 10 x 10 mm cellulose membrane obtained through biosynthesis using Acetobacter xylinum bacteria was implanted into the lumbar subcutaneous tissue of each mouse. The mice were euthanatized at seven, 15, 30, 60, and 90 days, and the membrane and surrounding tissues were collected and examined by histology.Results: A mild inflammatory response without foreign body reaction was observed until 30 days post-surgery around the implanted membrane. Polarized microscopy revealed that the membrane remained intact at all evaluation points. Scanning electron microscopy of the cellulose membrane surface showed absence of pores. The in vitro evaluation of the interaction between cells and biomaterial was performed through viability staining analysis of the cells over the biomaterial, which showed that 95% of the mesenchymal stem cells aggregating to the cellulose membrane were alive and that 5% were necrotic. Scanning electron microscopy showed mesenchymal stem cells with normal morphology and attached to the cellulose membrane surface.Conclusion: The microbial cellulose membrane evaluated was found to be nonresorbable, induced a mild inflammatory response and may prove useful as a scaffold for mesenchymal stem cells.